REVISIÓN SOBRE LA RELACIÓN DEL GENOTIPO PARA APOE4 Y EL DESARROLLO DE DEMENCIA TIPO ALZHEIMER - Román Garita, Nórbel (2011)
Introduction: Alzheimer’s disease is the mostcommon cause of dementia. Although there is anearly manifestation of 3 dominant autosomalgenes, they only explain between 1-2% of allcases. Efforts are made to establish the genetic risk for early diagnosis of the disease. Method:There are many scientific studies related to pre-vention, diagnosis and treatment of Alzheimer-type dementia. This review focuses on the pres-ence of the ApoE gene and its relationship to thedevelopment and progression of the disease.Conclusions: Alzheimer type dementia has mul-tifactorial origin; however, for late-onset casesthe presence of the ApoE4 genotype is an im-portant biomarker of risk factor.